Visionary Leadership of School Principals in Building Teacher Discipline in Vocational High Schools in Gowa Regency - Sirajuddin; Suhaedah; Muhammad Nusran; Hasanuddin; Amal Nur; Erwin Agus; Muh. Nasrun (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
This study aims to gain a deep understanding of how principals formulate, communicate, and implement their leadership vision in school management practices, particularly in relation to teacher discipline. The study employed a descriptive qualitative approach, involving the principal, vice principal, and teachers as informants. Data collection techniques included in-depth interviews, observation, and documentation. The results indicate that the principal's visionary leadership is reflected in the principal's ability to clearly and consistently explain the school's vision to all school members, exemplify it in daily leadership behavior, and develop the vision in accordance with the school's needs and challenges. This visionary leadership positively contributes to improved teacher discipline, demonstrated through adherence to school rules, punctuality in carrying out tasks, and increased professional responsibility. This study concludes that the principal's visionary leadership plays a strategic role in shaping a culture of teacher discipline in vocational high schools.